(untitled) (Bangladesh Journal of Otorhinolaryngology, 2012)
Introduction: This study aimed to compare the clinico-pathological features of the tubotympanic and atticoantral variety of chronic suppurative otitis media (CSOM). Methods: This was a cross sectional observational study conducted in the department of Otolaryngology Head & Neck Surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU) and Dhaka Medical College Hospital (DMCH), Dhaka, Bangladesh. The study was done over a period of six months and a total of 60 cases were selected. In group A 30 cases of CSOM tubotympanic variety were included while in group B 30 cases of atticoantral variety of CSOM were selected. The two groups were compared with regard to their clinical presentations, the type and degree of hearing loss and their associated complications by taking a detailed history followed by clinical examination and doing the relevant investigations. Results: In group A, the patients presented with a profuse non smelly discharge. All had a central perforation and majority had mild conductive hearing loss. There were no associated complications. In group B, the aural discharge were foul smelling and scanty. The perforations were 66% in the attic while 33.3% had marginal perforations. The hearing loss was mainly conductive in nature but in group B its more severe in degree and also there were more associated severe to profound sensori-neural hearing loss. There were also associated extracranial and intracranial complications in group B patients. Conclusion: The atticoantral variety of CSOM is associated with a foul smelling scanty discharge with severe hearing loss and complications than the tubotympanic variety of CSOM. Therefore early detection becomes essential especially in the primary care setting for appropriate referral to higher centers for better management DOI:http://dx.doi.org/10.3329/bjo.v18i2.11991 Bangladesh J Otorhinolaryngol 2012; 18(2): 138-144